First Molecular Confirmation of Equine Ocular Setaria digitata in China - Feng Yu; Bo Liu; Shulei Chen; Ziwen Yi; Xianyong Liu; Yiping Zhu; Jing Li (Veterinary Sciences, 2021)
A 5-year-old Mongolian mare (Equus caballus Linnaeus, 1758) was observed to have corneal opacity and excessive ocular discharge. An ophthalmic examination revealed a moving thread-like cylindrical worm in the anterior chamber of the right eye. The parasite was successfully removed surgically. The worm was observed under light microscopy and confirmed as Setaria digitata by 12S rRNA gene amplification and sequencing. Phylogenetic analysis demonstrated similarity with Setaria digitata in the National Center for Biotechnology Information (NCBI) GenBank database isolated from other Asian countries. This report is the first confirmed case of equine ocular setariasis by molecular diagnosis in China, which may indicate its presence in livestock and promote research on its epidemiology.